Empirical Research of Fans’ Consumption in China’s Talent Show Economy - Sun, Wei; Shin, Hoyoung; Kim, Kisu; Li, Rongrong (Journal of Accounting, Business and Finance Research, 2021)
In recent years, with the continuous development of China’s draft industry, internet drafts have become common throughout China. The talent show industry has not only won the love of audiences, but also the attention of capital. A lot of capital was invested in the talent show industry to cultivate new popular idols. Through social media platforms, fans can purchase products recommended by idols and vote for idols to increase their ranking. Idols also gain more popularity and sell more endorsed products through interactions with fans. Through questionnaire surveys and empirical methods, this study explores the factors that affect fans’ consumption of idols. Diversified participation, idols’ abilities, social influence, and empathy have been proven to have positive impacts on fans’ intention to consume. This research provides detailed empirical evidence regarding China’s talent show market, which has a strong role in promoting the sustainable development of the talent show economy.